Implementasi Transformasi Digital dan Green Marketing dalam Penetapan Merek Berkelanjutan di Era Teknologi - Seprinel Putri; Himyar Pasrizal (Lembaga Yasin AlSys, 2025)
The rapid development of digital technology and the growing awareness of environmental issues have significantly influenced brand development strategies in the era of Industry 5.0. This study aims to analyze the integration of digital transformation and green marketing strategies in achieving sustainable branding. A qualitative descriptive literature review method was used, focusing on publications from 2015 to 2025, complemented by content analysis to explore the interrelation between these two strategic approaches. The study is grounded in the theoretical frameworks of the Triple Bottom Line and Resource-Based View to understand the dimensions of sustainability and competitive advantage. The analysis reveals that digital transformation enhances operational efficiency, transparency, and business innovation, while green marketing strengthens brand image and increases consumer loyalty. Their integration results in the emergence of an eco-digital branding model, which combines digital technologies such as big data, the Internet of Things (IoT), artificial intelligence (AI), and blockchain with environmentally friendly practices in product innovation, communication strategies, and supply chain management. The study concludes that the synergy between digital transformation and green marketing not only reinforces brand sustainability but also fosters a new paradigm in brand management that simultaneously contributes to social and environmental responsibility.